A small-molecule inhibitor of the Wnt pathway (SM04690) as a potential disease modifying agent for the treatment of osteoarthritis of the knee. Issue 1 (January 2018) - Deshmukh, V.; Hu, H.; Barroga, C.; Bossard, C.; KC, S.; Dellamary, L.; Stewart, J.; Chiu, K.; Ibanez, M.; Pedraza, M.; Seo, T.; Do, L.; et al.
Summary: Objectives: Osteoarthritis (OA) is a degenerative disease characterized by loss of cartilage and increased subchondral bone within synovial joints. Wnt signaling affects the pathogenesis of OA as this pathway modulates both the differentiation of osteoblasts and chondrocytes, and production of catabolic proteases. A novel small-molecule Wnt pathway inhibitor, SM04690, was evaluated in a series of in vitro and in vivo animal studies to determine its effects on chondrogenesis, cartilage protection and synovial-lined joint pathology. Design: A high-throughput screen was performed using a cell-based reporter assay for Wnt pathway activity to develop a small molecule designated SM04690. Its properties were evaluated in bone-marrow-derived human mesenchymal stem cells (hMSCs) to assess chondrocyte differentiation and effects on cartilage catabolism by immunocytochemistry and gene expression, and glycosaminoglycan breakdown. In vivo effects of SM04690 on Wnt signaling, cartilage regeneration and protection were measured using biochemical and histopathological techniques in a rodent acute cruciate ligament tear and partial medial meniscectomy (ACLT + pMMx) OA model. Results: SM04690 induced hMSC differentiation into mature, functional chondrocytes and decreased cartilage catabolic marker levels compared to vehicle. A single SM04690 intra-articular (IA) injection was efficacious in a rodent OA model, with increased cartilage thickness, evidence for cartilage regeneration, and protection from cartilage catabolism observed, resulting in significantly improved Osteoarthritis Research Society International (OARSI) histology scores and biomarkers, compared to vehicle. Conclusions: SM04690 induced chondrogenesis and appeared to inhibit joint destruction in a rat OA model, and is a candidate for a potential disease modifying therapy for OA.